Identifying high-risk population of depression: association between metabolic syndrome and depression using a health checkup and claims database - Takahiro Imaizumi; Takuya Toda; Michitaka Maekawa; Daisuke Sakurai; Yuta Hagiwara; Yasuko Yoshida; Masahiko Ando; Shoichi Maruyama (Scientific Reports, 2022)
Abstract Depression and metabolic syndrome (MetS) are correlated, leading to an increased healthcare burden and decreased productivity. We aimed to investigate the association between MetS-related factors and depression using a health checkup and claims database. Individuals aged 18–75 years who underwent health examinations between 2014 and 2019 were enrolled in the study. Among 76,277 participants, “ever” and “incident” antidepressant users exhibited worse metabolic profiles and were more likely to be prescribed hypnotics and anxiolytics than “never” users. In a nested case–control study with a 1:10 ratio of incident users to controls, MetS was associated with incident antidepressant use (odds ratio, 1.53 [95% confidence interval 1.24–1.88]) adjusted for lifestyle information obtained from a self-administered questionnaire, medical history, and medications. Other metabolic traits also showed significant associations: body mass index (1.04 [1.02–1.06]), abdominal circumference per 10 cm (1.17 [1.08–1.27]), high blood pressure (1.17 [1.00–1.37]), glucose intolerance (1.29 [1.05–1.58]), and dyslipidemia (1.27 [1.08–1.51]). A bodyweight increase > 10 kg from age 20 years (1.46 [1.25–1.70]) was also significantly associated with incident antidepressant use. In conclusion, metabolic abnormalities were associated with incident antidepressant use and can be useful in identifying populations at high risk of depression.